Implementation of Lean Hospital in the Pharmacy Service at the Outpatient Department of a General Hospital - Jayanti, Irma; Felix Kasim; Sri Melda Br Bangun (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: The medication service at the Outpatient Pharmacy of RSUD Drs. H. Amri Tambunan experiences long waiting times, especially for BPJS guarantee prescriptions, which contradicts the established service time standards, i.e., dispensing medications ? 30 minutes and preparing compounded medications ? 60 minutes, in accordance with health service regulations. Research Objective: This study aims to analyze the waiting times for medication services at the Outpatient Pharmacy, identify types of waste within the service process flow, and identify factors that hinder service efficiency. Additionally, the study aims to provide recommendations for improvement to reduce waiting times and enhance service quality. Research Method: This qualitative study uses Value Stream Mapping (VSM) to analyze the medication service process and identify waste in each service stage. Additionally, a fishbone diagram is used to identify root causes affecting waiting times. Data is collected through interviews with pharmacy staff, the head of the pharmacy installation, and direct field observations. Research Results: This study found various types of waste in each stage of the medication service, including waiting, motion, defects, and overproduction. Factors hindering service time include patient congestion during peak hours, medication unavailability, and prescription inconsistencies with the formularium. Suboptimal use of information systems and a shortage of pharmacists were also identified as major hindrances. Conclusion: Improvements in process flow, coordination between departments, routine training, and the implementation of an integrated hospital management information system are needed to minimize waste and expedite service times at the Outpatient Pharmacy of RSUD Drs. H. Amri Tambunan.